Computer Engineering Education - Wolf, Marilyn; Madsen, Jan (Computer (Long Beach, Calif.), 2023)
The global semiconductor renaissance gives impetus to an examination of computer engineering curricula. Computer engineering encompasses hardware and software aspects of computer system design, often with an application-driven focus.